Vector Controlled Drives Of Permanent Magnet Synchronous Motor Using Pi Speed Controller For Long Cable Application - Cheok, Yong Seng; Zulkifilie, Ibrahim (2011)
This paper present a vector controlled drives of Permanent Magnet Synchronous Motor (PMSM) by using Proportional-Integral (PI) Speed controller for long cable application. As known, long cable caused an over voltage problem at motor terminal and could be double from the pulse output voltage at inverter terminal. This caused instability of the speed performances. PI speed controller is implemented to drive a PMSM with different cables length to investigated the speed performances, load disturbances and parameter variations of the system. Hysteresis current controller is used for inner loop current control and PI controller for outer loop speed control. Simulation results are provided to show performances on different cable length driving a PMSM.